1995
DOI: 10.2337/diacare.18.2.234
|View full text |Cite
|
Sign up to set email alerts
|

Independent Correlation Between Plasma Lipoprotein(a) and Angiographie Coronary Artery Disease in NIDDM

Abstract: Plasma Lp(a) is a strong and independent correlate of the extent of angiographic CAD in symptomatic patients with NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 10 publications
0
9
2
Order By: Relevance
“…Several studies showed that Lp(a) levels were associated with CAD extent and progressions in the general population [28,29,30,31], and the group of type II diabetic patients [32, 33]. In addition, some studies showed that Lp(a) levels and apo(a) polymorphism are associated with CAD severity [32, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that Lp(a) levels were associated with CAD extent and progressions in the general population [28,29,30,31], and the group of type II diabetic patients [32, 33]. In addition, some studies showed that Lp(a) levels and apo(a) polymorphism are associated with CAD severity [32, 34].…”
Section: Discussionmentioning
confidence: 99%
“…12,13,17 Data from Watts et al 12 group containing 36 diabetics with coronary angiography in 1995 and Gazzaruso et al 13 group enrolling 227 CAD patients with diabetes in 2006 suggested that Lp(a) might be a reliable predictor of CAD severity in type 2 diabetic patients, whereas the study performed by Pedreno et al 17 in 2000 suggested that there was lack of an association in CAD patients with diabetics (n = 355, 101 patients with diabetes and 254 patients without diabetes). In this study, we investigated the relationship between Lp(a) and the severity of new-onset CAD in patients with diabetes in a relatively large sample size and compared with those without diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, although Lp(a), used as a unique cardiovascular risk factor, has been widely, intensively studied for many years, particularly in recent years, whether the level of Lp(a) is an independent risk factor for CVD remains controversial till now. [8][9][10][11][12][13] Several studies indicated that Lp(a) might initiate atherosclerosis 14,15 and possibly promote thrombosis at very high levels, 16 while other data did not support the notion that Lp(a) was an independent predictor for CVD risk. 17 At the same time, few studies have analysed the relationship between serum Lp(a) levels and the severity of coronary artery disease (CAD), in particular using the well-recognized quantitative coronary scores in a large sample size.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that Lp(a) lipoprotein, which is associated with coronary heart disease in Type II diabetes [26,27], is an acutephase protein [9,28]. 2 A model for the role of cytokines and the innate immune system in the aetiology of Type II diabetes.…”
Section: Evidence For An Acute-phase Response In Type II Diabetesmentioning
confidence: 99%